DESIGN AND PERFORMANCE SIMULATION OF STRUCTURED MICROWAVE ABSORBER BASED ON CONDUCTIVE ABS 3D PRINTING FILAMENT - Abdullahi, M. B.; ali, M. H. (FUDMA JOURNAL OF SCIENCES, 2021)
Electromagnetic absorbing materials with broadband, lightweight, wide-angle, and polarization-insensitive characteristics attracts extensive research interest recently, due to rapid advancement in radar detection techniques and communication devices. Three-dimensional printing is being employed to realize cost-effective structured electromagnetic absorbers that has lately become a common practice of improving radar stealth performance and shielding effectiveness. Structured absorbers permit realization of desired absorption characteristics by careful design of their geometrical structures. In this study, a two-layer structured microwave absorber using conductive ABS polymer is simulated. COMSOL Multiphysics environment is used to investigate the absorption characteristics of the designed structure. Under normal incidence, simulation results revealed at least 90% of absorption from 7.2 GHz to 18.0 GHz for both Transverse Electric (TE) and Transverse Magnetic (TM) polarizations. Oblique incidence results for TE polarization indicate that the absorption rate is more than 90% in the whole range of 7.2–18 GHz frequency band up to 450 while the absorption rate is more than 80% for 600 incident waves. The absorption rate is more than 90% in the 7.2-18 GHz range for oblique incidences of up to 300 only for TM polarization, but greater than 70% at 450 incident angles. Additionally, the designed absorber is independent of the polarization of the incident wave. As a result of the exhibited favourable absorption characteristics, the studied absorber provides great potentials for its experimentation and practicability using the low-cost 3D printing manufacturing process